Enablers, barriers and strategies to build resilience among cancer survivors: a qualitative study protocol - Fernandes, Júlio Belo; Domingos, Josefa; Almeida, Ana Silva; Castro, Cidália; Simões, Aida; Fernandes, Sónia; Vareta, Diana; Bernardes, Catarina; Fonseca, Jorge; Vaz, Célia; Dias, Ana Rita; Fernandes, Tatiana; et al. (Frontiers in Psychology, 2023)
Cancer is a life-threatening illness affecting all dimensions of a person's health. Cancer survivors must build resilience to face this adversity and continue their life projects. The present study explores the enablers, barriers, and strategies to build resilience among cancer survivors. This qualitative, descriptive exploratory study will use purposive sampling to recruit cancer survivors and healthcare professionals from two hospital centers in Lisbon and Tagus Valley. Interviews will be conducted until data saturation occurs. Data analysis will be performed using an inductive content analysis process with the help of the QDA Miner Lite database. The findings from this study will generate knowledge that may help stakeholders to identify effective strategies to build resilience among cancer survivors. By implementing strategies to foster resilience, healthcare professionals can potentially promote positive adaptations to cancer by strengthening resilience enablers and reducing the impact of barriers.